2022
DOI: 10.2147/idr.s365728
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Knowledge, Attitude and Practice of Hepatitis B Among Freshmen in Jiangsu Based on Lasso-Logistic Regression and Structural Equation Model

Abstract: Objective We aimed to describe the knowledge, attitude and practice (KAP) status of hepatitis B virus (HBV) among freshmen who were in the class of 2020 and from Jiangsu Province. Methods A random multistage sampling had been used to screen freshmen to conduct online questionnaire. The chi-square test was applied for pairwise comparison between sub-groups. Lasso regression and logistic regression were used to analyze the influencing factors of KAP about HBV. A structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Researchers in Lahore in Pakistan surveyed 2,800 students across six different universities and found that students had fair levels of knowledge, but that significant gaps existed particularly in relation to awareness of the hepatitis B vaccine [ 18 ]. Research among freshman in the Jiangsu province in China found that knowledge of the virus was low, particularly among students whose fathers had lower education levels [ 19 ]. In a study among university students in Scotland, including students from countries with high hepatitis B prevalence, students reported having low levels of knowledge and felt that their risk of acquiring the infection was low, but felt confident to access health care if needed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in Lahore in Pakistan surveyed 2,800 students across six different universities and found that students had fair levels of knowledge, but that significant gaps existed particularly in relation to awareness of the hepatitis B vaccine [ 18 ]. Research among freshman in the Jiangsu province in China found that knowledge of the virus was low, particularly among students whose fathers had lower education levels [ 19 ]. In a study among university students in Scotland, including students from countries with high hepatitis B prevalence, students reported having low levels of knowledge and felt that their risk of acquiring the infection was low, but felt confident to access health care if needed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%